Higher field reduced FOV diffusion-weighted imaging for abdominal imaging at 5.0 Tesla: image quality evaluation compared with 3.0 Tesla - Zhang, Yunfei; Sheng, Ruofan; Yang, Chun; Dai, Yongming; Zeng, Mengsu (Insights into imaging, 2023)
Objective To evaluate the image quality of reduced field-of-view (rFOV) DWI for abdominal imaging at 5.0 Tesla (T) compared with 3.0 T. Methods Fifteen volunteers were included into this prospective study. All the subjects underwent the 3.0 T and 5.0 T MR examinations (time interval: 2 ± 1.9 days). Free-breathing (FB), respiratory-triggered (RT), and navigator-triggered (NT) spin-echo echo-planner imaging-based rFOV-DWI examinations were conducted at 3.0 T and 5.0 T (FB 3.0 T , NT 3.0 T , RT 3.0 T , FB 5.0 T , NT 5.0 T , and RT 5.0 T ) with two b values ( b = 0 and 800 s/mm 2 ), respectively. The signal-to-noise ratio (SNR) of different acquisition approaches were determined and statistically compared. The image quality was assessed and statistically compared with a 5-point scoring system. Results The SNRs of any 5.0 T DWI images were significantly higher than those of any 3.0 T DWI images for same anatomic locations. Moreover, 5.0 T rFOV-DWIs had the significantly higher sharpness scores than 3.0 T rFOV-DWIs. Similar distortion scores were observed at both 3.0 T and 5.0 T. Finally, RT 5.0 T displayed the best overall image quality followed by NT 5.0 T , FB 5.0 T , RT 3.0 T , NT 3.0 T and FB 3.0 T (RT 5.0 T = 3.9 ± 0.3, NT 5.0 T = 3.8 ± 0.3, FB 5.0 T = 3.4 ± 0.3, RT 3.0 T = 3.2 ± 0.4, NT 3.0 T = 3.1 ± 0.4, and FB 3.0 T = 2.7 ± 0.4, p < 0.001). Conclusion The 5.0 T rFOV-DWI showed better overall image quality and improved SNR compared to 3.0 T rFOV-DWI, which holds clinical potential for identifying the abdominal abnormalities in routine practice. Critical relevance statement This study provided evidence that abdominal 5.0 Tesla reduced field of view diffusion-weighted imaging (5.0 T rFOV-DWI) exhibited enhanced image quality and higher SNR compared to its 3.0 Tesla counterparts, holding clinical promise for accurately visualizing abdominal abnormalities. Key points • rFOV-DWI was firstly integrated with high-field-MRI for visualizing various abdominal organs. • This study indicated the feasibility of abdominal 5.0 T-rFOV-DWI. • Better image quality was identified for 5.0 T rFOV-DWI. Graphical Abstract